IMPLEMENTATION OF LAW AS TO MAINTAIN SECURITY IN THE CONTEXT OF PROFESSIONAL POLICE POLMAS (CASE STUDY IN LAMPUNG POLICE) - Muhammad Yaman; Erlyn Indarti (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
The reform process has been and is ongoing to reach a democratic civil society led to various changes in the joints and a country life. Police are currently carrying out a process of reform to become a civilian police force, must be able to adapt to the development of community life by way of changing the paradigm that drip-focus on a reactive approach and conventional (power) to a proactive approach and gained public support with an emphasis on partnerships in the framework of solving social problems. The police function of organizing models known in foreign countries with different names like Neighborhood Policing, Community Oriented Policing, Community Based Policing, and eventually popular as Community Policing. Important issues as the problem of police (police problem) from the point of view of the community, such as the application of the discriminatory law, the presumption of the police, the use of inappropriate police diskresi is not an easy job to be resolved in the framework of the reform of the national police. Despite this realization that Police in democratic societies is basically a job managing a conflict needs to be grown and realized through programs of police-community relations, in addition to the existence of institutions supported controls. Policy implementation of the police force in General, is based on the desire to prevent abuse of police authority, to protect the rights and liberties of the people, so that the police are working in accordance with the law, and that there is oversight of police activities against. Transparency and accountability of the national police in the past can be said to be low among others due to the lack of openness, the general public is less informed about the activities of police handling and handling complaints or statements. Meanwhile, traditionally the national police so far have actually developed a mentoring program Community (Bimmas) and programs related to security system Swakarsa (Siskamswakarsa). The program Siskamswakarsa is realized through the system's security environment (Siskamling) which includes the neighborhoods, environmental education, and the work environment as a form of security Swakarsa as defined in the Police Act of the Republic of Indonesia. Babinkamtibmas (Enlisted the coaching Community security and public order) Actas the spear head of the implementation Siskamswakarsa/Siskamling. But it needs to be underlined, patterns are the implementation of the national police that is ' preemit ' through Bimmas approach/Babinkamtibmas it surely also implies structural relations of power, so the perceived need to adapted to the development of civil society. On the basis of the considerations outlined above, is seen necessary to adopt the concept of Community Policing and customize it to the characteristics and needs of the community as well as by way of Indonesia and with the name of Indonesia. Without prejudice to the possibility of the use of a different term translations, especially for academic purposes, formally by the ranks of the police and the model was named the community Perpolisian. Further conceptual and operational terms mean shortened Polmas. Thoughts concerning the development of Polmas seen needs to be poured in a manuscript policy and strategy of the organization. To that end, throughDecree No. Kapolri Pol. SKEP/737/X/2005 October 13, 2005, has been proclaimed policiesand strategies of the application of Community Perpolisian Model (Polmas) in order of organizing task [subject matter] the national police. As the motor or spearhead implementation of Polmas Police Partnership Forum was the establishment of communities (FKPM) at the level of the operational units of the national police as a container of communication, consultation, transparency, and accountability of the national police with the community it serves. In connection with this, the idea of polmas got a first step on Grand Strategy (Renstra) national police 25 years as already mentioned above, namely: 1) short term (2005-2010), building Trust Building; 2) medium term (2011-2015), establish Partnership/Networking; 3) long term (2016-2025), embodies the Strive for Excellence.